Specific issues in terminating the lease agreement due to the liquidation of a legal entity as part of the bankruptcy process - Trufanova, Yuliia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The peculiarities of terminating the lease (rent) agreement in connection with the liquidation of a legal entity are disсussed. It was clarified that the start of a liquidation procedure does not terminate a lease (rent) agreement. The scientific opinion is maintained, that the lease (rent) agreement is terminated from the moment the termination of the legal entity is entered into the USR.